Deviance & social control - Deutschmann, Linda Bell. (Toronto : ITP Nelson, 1998)
Written with a Canadian focus, this text examines deviance from many perspectives with the aim of providing a balanced and comprehensive view. Historical and contemporary theoretical perspectives are used to show that our ideas about behaviour are not static, but changing."--Cover.
Includes bibliographical references and index.
Keywords: Deviant behavior; Social control